2
$\begingroup$

Given the heat equation:

$$\partial_{t}{\varPhi(x,t)}=k^2\partial_{xx}{\varPhi(x,t)}$$

with the boundary conditions:

$$\Phi(x,0)=\Phi_0$$

and a Neumann boundary condition of the kind:

$${\partial_{x}}{\Phi(0,t)=\nu(t)+C}$$

where $\nu(t)$ is a stochastic variable with gaussian distribution ${\sigma=\sigma_0,\mu=0}$ and $C$ a constant, what is the distribution of the $\Phi(L,t)$?

Thanks in advance

$\endgroup$
8
$\begingroup$

Of course use separation of variables:

Let $\varPhi(x,t)=X(x)T(t)$ ,

Then $X(x)T'(t)=k^2X''(x)T(t)$

$\dfrac{T'(t)}{T(t)}=\dfrac{k^2X''(x)}{X(x)}=-s^2$

$\begin{cases}\dfrac{T'(t)}{T(t)}=-s^2\\k^2X''(x)+s^2X(x)=0\end{cases}$

$\begin{cases}T(t)=c_3(s)e^{-ts^2}\\X(x)=\begin{cases}c_1(s)\sin\dfrac{xs}{k}+c_2(s)\cos\dfrac{xs}{k}&\text{when}~s\neq0\\c_1x+c_2&\text{when}~s=0\end{cases}\end{cases}$

$\therefore\varPhi(x,t)=C_1x+C_2+\int_0^\infty C_3(s^2)e^{-ts^2}\sin\dfrac{xs}{k}ds+\int_0^\infty C_4(s)e^{-ts^2}\cos\dfrac{xs}{k}ds$

$\partial_{x}\varPhi(x,t)=C_1+\int_0^\infty\dfrac{C_3(s^2)se^{-ts^2}}{k}\cos\dfrac{xs}{k}ds-\int_0^\infty\dfrac{C_4(s)se^{-ts^2}}{k}\sin\dfrac{xs}{k}ds$

$\partial_{x}\varPhi(0,t)=\nu(t)+C$ :

$C_1+\int_0^\infty\dfrac{C_3(s^2)se^{-ts^2}}{k}ds=\nu(t)+C$

$\int_0^\infty\dfrac{C_3(s^2)e^{-ts^2}}{2k}d(s^2)=\nu(t)+C-C_1$

$\int_0^\infty\dfrac{C_3(s)e^{-ts}}{2k}ds=\nu(t)+C-C_1$

$\dfrac{1}{2k}\mathcal{L}_{s\to t}\{C_3(s)\}=\nu(t)+C-C_1$

$C_3(s)=2k\mathcal{L}^{-1}_{t\to s}\{\nu(t)\}+2k(C-C_1)\delta(s)$

$\therefore\varPhi(x,t)=C_1x+C_2+2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}e^{-ts^2}\sin\dfrac{xs}{k}ds+2k(C-C_1)\int_0^\infty\delta(s^2)e^{-ts^2}\sin\dfrac{xs}{k}ds+\int_0^\infty C_4(s)e^{-ts^2}\cos\dfrac{xs}{k}ds=C_1x+C_2+2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}e^{-ts^2}\sin\dfrac{xs}{k}ds+2k(C-C_1)\int_0^\infty\delta(s)e^{-ts}\sin\dfrac{x\sqrt{s}}{k}d(\sqrt{s})+\int_0^\infty C_4(s)e^{-ts^2}\cos\dfrac{xs}{k}ds=C_1x+C_2+2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}e^{-ts^2}\sin\dfrac{xs}{k}ds+2k(C-C_1)\int_0^\infty\dfrac{\delta(s)e^{-ts}}{2\sqrt{s}}\sin\dfrac{x\sqrt{s}}{k}ds+\int_0^\infty C_4(s)e^{-ts^2}\cos\dfrac{xs}{k}ds=C_1x+C_2+2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}e^{-ts^2}\sin\dfrac{xs}{k}ds+2k(C-C_1)\lim_{s\to0}\dfrac{e^{-ts}\sin\dfrac{x\sqrt{s}}{k}}{2\sqrt{s}}+\int_0^\infty C_4(s)e^{-ts^2}\cos\dfrac{xs}{k}ds=C_1x+C_2+2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}e^{-ts^2}\sin\dfrac{xs}{k}ds+2k(C-C_1)\lim_{s\to0}\dfrac{\dfrac{xe^{-ts}}{2k\sqrt{s}}\cos\dfrac{x\sqrt{s}}{k}-te^{-ts}\sin\dfrac{x\sqrt{s}}{k}}{\dfrac{1}{\sqrt{s}}}+\int_0^\infty C_4(s)e^{-ts^2}\cos\dfrac{xs}{k}ds=C_1x+C_2+2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}e^{-ts^2}\sin\dfrac{xs}{k}ds+2k(C-C_1)\lim_{s\to0}\biggl(\dfrac{xe^{-ts}}{2k}\cos\dfrac{x\sqrt{s}}{k}-t\sqrt{s}e^{-ts}\sin\dfrac{x\sqrt{s}}{k}\biggr)+\int_0^\infty C_4(s)e^{-ts^2}\cos\dfrac{xs}{k}ds=C_1x+C_2+2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}e^{-ts^2}\sin\dfrac{xs}{k}ds+(C-C_1)x+\int_0^\infty C_4(s)e^{-ts^2}\cos\dfrac{xs}{k}ds=Cx+C_2+2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}e^{-ts^2}\sin\dfrac{xs}{k}ds+\int_0^\infty C_4(s)e^{-ts^2}\cos\dfrac{xs}{k}ds$

$\varPhi(x,0)=\varPhi_0$ :

$Cx+C_2+2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}\sin\dfrac{xs}{k}ds+\int_0^\infty C_4(s)\cos\dfrac{xs}{k}ds=\varPhi_0$

$\int_0^\infty C_4(s)\cos\dfrac{xs}{k}ds=-Cx+\varPhi_0-C_2-2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}\sin\dfrac{xs}{k}ds$

$\int_0^\infty C_4(s)\cos xs~ds=-Ckx+\varPhi_0-C_2-2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}\sin xs~ds$

$\mathcal{F}_{c,s\to x}\{C_4(s)\}=-Ckx+\varPhi_0-C_2-2k\mathcal{F}_{s,s\to x}\{\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}\}$

$C_4(s)=\dfrac{2Ck}{\pi s^2}+(\varPhi_0-C_2)\delta(s)-2k\mathcal{F}^{-1}_{c,x\to s}\{\mathcal{F}_{s,s\to x}\{\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}\}\}$

$\therefore\varPhi(x,t)=Cx+C_2+2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}e^{-ts^2}\sin\dfrac{xs}{k}ds+\dfrac{2Ck}{\pi}\int_0^\infty\dfrac{e^{-ts^2}}{s^2}\cos\dfrac{xs}{k}ds+(\varPhi_0-C_2)\int_0^\infty\delta(s)e^{-ts^2}\cos\dfrac{xs}{k}ds-2k\int_0^\infty\mathcal{F}^{-1}_{c,x\to s}\{\mathcal{F}_{s,s\to x}\{\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}\}\}e^{-ts^2}\cos\dfrac{xs}{k}ds=Cx+C_2+\dfrac{2Ck}{\pi}\int_0^\infty\dfrac{e^{-ts^2}}{s^2}\cos\dfrac{xs}{k}ds+2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}e^{-ts^2}\sin\dfrac{xs}{k}ds+\varPhi_0-C_2-2k\int_0^\infty\mathcal{F}^{-1}_{c,x\to s}\{\mathcal{F}_{s,s\to x}\{\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}\}\}e^{-ts^2}\cos\dfrac{xs}{k}ds=Cx+\varPhi_0+\dfrac{2Ck}{\pi}\int_0^\infty\dfrac{e^{-ts^2}}{s^2}\cos\dfrac{xs}{k}ds+2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}e^{-ts^2}\sin\dfrac{xs}{k}ds-2k\int_0^\infty\mathcal{F}^{-1}_{c,x\to s}\{\mathcal{F}_{s,s\to x}\{\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}\}\}e^{-ts^2}\cos\dfrac{xs}{k}ds$

Hence $\varPhi(L,t)=CL+\varPhi_0+\dfrac{2Ck}{\pi}\int_0^\infty\dfrac{e^{-ts^2}}{s^2}\cos\dfrac{Ls}{k}ds+2k\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}e^{-ts^2}\sin\dfrac{Ls}{k}ds-2k\int_0^\infty\mathcal{F}^{-1}_{c,L\to s}\{\mathcal{F}_{s,s\to L}\{\mathcal{L}^{-1}_{t\to s^2}\{\nu(t)\}\}\}e^{-ts^2}\cos\dfrac{Ls}{k}ds$

$\endgroup$
  • $\begingroup$ Nice solution $\Phi(L,t)$ for the given $v(t)$. However, it is not the distribution of $\Phi(L,t)$. $\endgroup$ – Hans Mar 19 at 8:04

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.